2023
DOI: 10.1136/rmdopen-2023-003455
|View full text |Cite
|
Sign up to set email alerts
|

Early axial spondyloarthritis according to the ASAS consensus definition: characterisation of patients and effectiveness of a first TNF inhibitor in a large observational registry

Adrian Ciurea,
Andrea Götschi,
René Bräm
et al.

Abstract: ObjectiveTo characterise the population fulfilling the Assessment of SpondyloArthritis international Society (ASAS) consensus definition of early axial spondyloarthritis (axSpA) and to determine the effectiveness of a first tumour necrosis factor inhibitor (TNFi) in early versus established axSpA in a large observational registry.MethodsA total of 3064 patients with axSpA in the Swiss Clinical Quality Management registry with data on duration of axial symptoms were included (≤2 years=early axSpA, N=658; >2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
0
1
Order By: Relevance
“…Similarly, in another study, concomitant diseases were associated with worse treatment effects with TNFi in axSpA [47]. In our study concomitant diseases did not significantly increase this risk (OR = 2.03, 95% CI 0.22 − 18.77, p = 0.53).…”
Section: Table 2 Baseline Predictors Of Treatment Failure To Bdmardssupporting
confidence: 76%
See 1 more Smart Citation
“…Similarly, in another study, concomitant diseases were associated with worse treatment effects with TNFi in axSpA [47]. In our study concomitant diseases did not significantly increase this risk (OR = 2.03, 95% CI 0.22 − 18.77, p = 0.53).…”
Section: Table 2 Baseline Predictors Of Treatment Failure To Bdmardssupporting
confidence: 76%
“…Zonulin was significantly correlated with CRP, although CRP alone was not associated with treatment response. This is a different result from most studies, which have shown the superiority of increased CRP in predicting good response to bDMARDs, especially TNFi [29,30,47,48]. However, higher values of the inflammatory indices (WBC, CRP, ESR) reduced the risk of poor response, but not significantly.…”
Section: Table 2 Baseline Predictors Of Treatment Failure To Bdmardscontrasting
confidence: 70%